Peran Etika Bisnis Apple Di Era Globalisasi - Kristelia Piri; Monica Ratulangi; Rahel Tengko; Ovelia Potangkuman; Cloudia Karepouwan; Grace Christien Sumakul (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study explores how Apple Inc. applies business ethics amid globalization, where rapid technological growth and global integration create new ethical challenges. Business ethics provide moral guidance crucial for sustaining corporate reputation and public trust. Using a descriptive qualitative method, this research analyzes secondary data from literature and case studies. The findings show Apple’s strong commitment to privacy, sustainability, and legal compliance. Key initiatives include user data protection, eco-friendly practices, and supplier responsibility. However, the company still faces criticism related to labor conditions, product accessibility, and alleged anti-competitive behavior. These findings highlight the importance of consistently upholding ethical standards to ensure business sustainability and global competitiveness.